A positive feedback regulatory loop, SA-AtNAP-SAG202/SARD1-ICS1-SA, in SA biosynthesis involved in leaf senescence but not defense response - Yaxin Wang; Bin Liu; Youzhen Hu; Su-Sheng Gan (Molecular Horticulture, 2022)
Abstract Salicylic acid (SA) is an important plant hormone that regulates defense responses and leaf senescence. It is imperative to understand upstream factors that regulate genes of SA biosynthesis. SAG202/SARD1 is a key regulator for isochorismate synthase 1 (ICS1) induction and SA biosynthesis in defense responses. The regulatory mechanism of SA biosynthesis during leaf senescence is not well understood. Here we show that AtNAP, a senescence-specific NAC family transcription factor, directly regulates a senescence-associated gene named SAG202 as revealed in yeast one-hybrid and in planta assays. Inducible overexpreesion of AtNAP and SAG202 lead to high levels of SA and precocious senescence in leaves. Individual knockout mutants of sag202 and ics1 have markedly reduced SA levels and display a significantly delayed leaf senescence phenotype. Furthermore, SA positively feedback regulates AtNAP and SAG202. Our research has uncovered a unique positive feedback regulatory loop, SA-AtNAP-SAG202-ICS1-SA, that operates to control SA biosynthesis associated with leaf senescence but not defense response.